Development of FM screens - Pinćjer, Ivan; Nedeljković, Uroš; Papić, Miloš (Journal of Graphic Engineering and Design, 2023)
What is a satisfactory quality when it comes to graphic arts industry? Acceptable quality of halftone image is become same as photographic picture. There are many different ways in which one can try to reach the desired quality. Different methods of halftoning (lpi and diferent methods of forming halftone dot), scanning, prepress, plate making are just some ways to influence the final printing result. Knowing the advantages and disadvantages of a certain halftoning technique will give us more ability to choose the right process path.